Sign Languages in Contact - Quinto-Pozos, David (Sociolinguistics in deaf communities series ;, 2007)
This volume collects for the first time various accounts of contact between sign languages throughout the world, presenting an exciting opportunity to further understand the structural and social factors of this linguistic component in deaf communities. Editor David Quinto-Pozos has divided Sign Languages in Contact into four parts, starting with Contact in a Trilingual Setting. The sole essay in this section features a study of Maori signs by Rachel McKee, David McKee, Kirsten Smiler, and Karen Pointon that reveals the construction of indigenous Deaf identity in New Zealand Sign Language. In Part Two: Lexical Comparisons, Jeffrey Davis conducts an historic, linguistic assessment of varieties of North American Indian sign languages. Daisuke Sasaki compares the Japanese Sign Language lexicon with that of Taiwan Sign Language by focusing on signs that share the same meaning and all parameters except for their handshapes. Judith Yoel's chapter takes up the entirety of Part Three: Language Attrition, with her analysis of the erosion of Russian Sign Language among immigrants to Israel. The final part describes how educators and other "foreign" visitors can influence indigenous sign languages. Karin Hoyer delineates the effects of international sign and gesture on Albanian Sign Language. Jean Ann, Wayne H. Smith, and Chiangsheng Yu close this significant collection by assessing contact between Mainland China's sign language and Taiwan Sign Language in the Ch'iying School in Taiwan.